Kształtowanie się przemysłu samochodów osobowych w krajach Europy Środkowej w latach 1997–2007 - Piotr Lizak (Prace Komisji Geografii Przemysłu Polskiego Towarzystwa Geograficznego, 2009)
Automotive industry belongs to one of the crucial branches of the Central European countries economy. It bears considerably on the economic situation of the country and on the level of employment in other sectors of industry, which provide for the automotive industry, as well as on other branches, like trade or services.Basing on the above assumptions, the article analyses the problem of development of the automotive industry in the Central European countries. The article describes the tendencies and the potential of the automotive industry development in particular countries, as well as the competitiveness of these countries with respect to the inflow of the new economic branch investments. In the paper, the spatial distribution of the new automotive industry investments and their locations are presented.The development of car manufacturing in the countries discussed was not parallel, yet all these countries display an increase tendency in the production level.The noticeable development of the automotive industry in these countries is connected with the inflow of foreign direct investments by international corporations. The biggest car manufacturing factories in Central Europe are located in Mlada Boleslav in the Czech Republic and in Trnava in Slovakia. The elementary factors that influenced the increasing competitiveness of Slovakia for the automotive industry were: political stability, fast development of the transportation infrastructure, convenient geographical location in the centre of Europe, at the crossroads of several transport routes, which enables access to the neighbouring markets, availability of qualified labour, and low work costs combined with satisfactory productivity levels.